2013
DOI: 10.4236/jmp.2013.412194
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Hybridization between Actinide 5<i>f</i> and Oxygen 2<i>p</i> Orbitals for Electronic Structure of Actinide Dioxides

Abstract: In order to promote our understanding on electronic structure of actinide dioxides, we construct a tight-binding model composed of actinide 5f and oxygen 2p electrons, which is called f-p model. After the diagonalization of the f-p model, we compare the eigen-energies in the first Brillouin zone with the results of relativistic band-structure calculations. Here we emphasize a key role of f-p hybridization in order to understand the electronic structure of actinide dioxides. In particular, it is found that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ultimately, we found that the orbitals of f-shell electrons simultaneously hybridize with the Ca and O orbitals on the long-range surface layer and short-range inner layer, due to the similar crystalline electric eld (CEF) potential energy, where the hopping integrals (f-p p and f-p s terms) in the f-p hybridization term of Hamiltonian formula by using Slater-Koster table provide the similar hopping amplitudes between f and p orbitals. 24 In this context, the electron transfer rates of the major constituents have the following order: Si-3p 2 $ Al-3p 1 ( Ca-4s 2 / d 0 < Ca-3p 6 < O-2p 4 . On the other hand, compared to that of 4f-shell electrons/ Ca-Mt, the orbital degeneracy of 5f-shell electrons/Ca-Mt reduces near the Fermi point, accelerating the electron transfer process at the conduction band and valence band.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, we found that the orbitals of f-shell electrons simultaneously hybridize with the Ca and O orbitals on the long-range surface layer and short-range inner layer, due to the similar crystalline electric eld (CEF) potential energy, where the hopping integrals (f-p p and f-p s terms) in the f-p hybridization term of Hamiltonian formula by using Slater-Koster table provide the similar hopping amplitudes between f and p orbitals. 24 In this context, the electron transfer rates of the major constituents have the following order: Si-3p 2 $ Al-3p 1 ( Ca-4s 2 / d 0 < Ca-3p 6 < O-2p 4 . On the other hand, compared to that of 4f-shell electrons/ Ca-Mt, the orbital degeneracy of 5f-shell electrons/Ca-Mt reduces near the Fermi point, accelerating the electron transfer process at the conduction band and valence band.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therein, the Coulomb repulsion between a 4f-shell electron and anion is shied towards weaker bonding with respect to the binding energy (4f-HRBE), and the author provided the 4f-electron binding energy relative to the vacuum energy (4f-VRBE). For the hybridisation between 5f-shell electron's orbital and O-2p 4 orbital, Hasegawa et al 24 investigated the f-p model, which is the more realistic Hamiltonian for the 5f-shell electron inuencing the O-2p 4 orbitals, to better understand the electronic structure of 5f-O-p. There has been a peculiar point in which the octupole phase only appears for the small absolute value of (f-p p)/(f-p s), where (f-p p) and (f-p s) are the Slater-Koster integrals between f and p orbitals.…”
Section: Introductionsmentioning
confidence: 99%